John Skelton and poetic authority defining the liberty to speak - Griffiths, Jane, 1970- (Oxford English monographs., 2006)
This work links John Skelton's poetic theory with his practice as a writer and translator. In reassessing Skelton's place in the English literary canon, it suggests the need to reconsider the conventional distinction between 'Medieval' and 'Renaissance' poetics.